EFEKTIVITAS PEMBELAJARAN BAHASA ARAB MASA PANDEMI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM (PAI) UNIVERSITAS MUHAMMADIYAH SURAKARTA - Nurhidayati Roisyah; Nurul Latifatul Inayati; Saifudin Saifudin (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2021)
The COVID-19 pandemic has had an impact on all fields, including education. During a pandemic like now, learning cannot be done face-to-face but is replaced with online learning. This affects the process of learning Arabic. This study aims to determine how the process of implementing Arabic language learning, the effectiveness of Arabic learning, and describing the obstacles in learning Arabic during the pandemic for students of the Islamic Religious Education Study Program. This research was conducted using qualitative research methods using a phenomenological approach. From the data collected, it shows that 1) The implementation of Arabic learning has been going well by the designed learning plan. In the Arabic language learning objectives, several achievements are divided into four categories, including the learning outcomes of attitudes and values, general skills learning outcomes, specific skills learning outcomes, and knowledge acquisition learning outcomes. The learning media used are google meet, zoom, Schoology, WhatsApp, PowerPoint, or pdf. The learning method used is the method of discussion and information search. The evaluation system uses assignments and a structured exam which is divided into two, namely the mid-semester exam and the end-semester exam. 2) The effectiveness of learning Arabic cannot be separated from the development of methods applied by teaching lecturers. The Group-Based Master Learning (GBML) method is one of the methods used to make it easier for students to learn. 3) two factors become obstacles in the process of learning Arabic. The first is the internal factor, namely, the different educational backgrounds of students and a sense of saturation due to online learning. The two external factors are signal constraints, time differences, and the number of quotas used in the learning process.